Islamic philanthropy and community welfare: Study of ZIS asset fundraising strategy and distribution in coastal Java, Indonesia - A. Zaenurrosyid; Hidayatus Sholihah; Rozihan (NUsantara Islamic Economic Journal, 2023)
Community economic empowerment can be done through the management and distribution of the allocation of zakat, infaq, and alms. Based on the goal of raising the humanitarian side, helping the community by optimizing the distribution of funds from ZIS fundraising is a good way. This distribution is especially for people affected by natural disasters such as pandemics. Therefore, the dynamics of governance, the diversity of distribution in the form of social capital from the allocation of ZIS funds to their managers becomes an interesting study to analyse so that it becomes a model for other institutions in finding solutions to the problems of the people that come to the surface. Moreover, legal support has been born, UUZ Number 23 of 2011 concerning the importance of zakat management and other regulations governing donations of people's funds. So that these assets can further empower the community to continue education, strengthen the culture of family harmony, as well economic prosperity. Through a qualitative approach from validated data, the research was carried out by kyai informants, leaders of Zakat institutions, and other managers. The results of this study indicate that philanthropic funds, zakat in the context of the northern coastal community of Java, namely in the Pati area can be collected massively, and from the community's perspective, they have increased their economy through various entrepreneurs. There are various kinds of community productive economic empowerment that have been managed well. Post-pandemic, this community empowerment program is focused on aspects of education, populist economy, and socio-religious.